Price as a determinant of a food product`s image - Baruk, Agnieszka Izabela (Wydawnictwo Politechniki Łódzkiej, 2015)
The article was to achieve two research goals, that is identifying and arranging hierarchically factors which influence the image of a food product and defining the place among them taken by the price. The article is of theoretical-empirical character. In the theoretical part of the article, the method of cognitive-critical analysis of world's marketing and marketing management literature was used In the research part, on the other hand, the method of questionnaires was used to gather primary data and also the method of factors' analysis to carry out statistical deduction. On the basis of research conducted it can be stated that the price of a food product is not a crucial determinant of its image. The first place in the hierarchical structure of image's determinants was taken by brand factor, whereas the last place went to the price. The knowledge of these factors and their hierarchical structure enables the bidders of food products to manage the image effectively and efficiently, which determines the value of research and conclusions drawn from their results.
Keywords: image; food product; price